2023
DOI: 10.1080/19768354.2023.2181217
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between endoplasmic reticulum stress response and autophagy in human diseases

Abstract: Cells activate protective mechanisms to overcome stressful conditions that threaten cellular homeostasis, including imbalances in calcium, redox, and nutrient levels. Endoplasmic reticulum (ER) stress activates an intracellular signaling pathway, known as the unfolded protein response (UPR), to mitigate such circumstances and protect cells. Although ER stress is sometimes a negative regulator of autophagy, UPR induced by ER stress typically activates autophagy, a self-degradative pathway that further supports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…In our dataset, genes and pathways related to apoptosis regulation and autophagy signaling were also dysregulated in astrocytes, oligodendrocytes, and in the neuronal clusters with reduced proportions in PSP. Although the relationship between the UPR and autophagy has been well studied in neurons, its role in regulating cell autonomous and non-cell autonomous functions in other cell types has not been well studied [81][82][83].…”
Section: Discussionmentioning
confidence: 99%
“…In our dataset, genes and pathways related to apoptosis regulation and autophagy signaling were also dysregulated in astrocytes, oligodendrocytes, and in the neuronal clusters with reduced proportions in PSP. Although the relationship between the UPR and autophagy has been well studied in neurons, its role in regulating cell autonomous and non-cell autonomous functions in other cell types has not been well studied [81][82][83].…”
Section: Discussionmentioning
confidence: 99%
“… 54 Both ERS and autophagy are crucial determinants of cell fate and require tight regulation. 55
Fig. 2 UPR-mediated autophagy and partial mechanisms.
…”
Section: Upr-mediated Cell Deathmentioning
confidence: 99%
“…As a result, it induces host cellular innate oxidative stress and proinflammatory immune responses leading to apoptotic cell death ( 14 ). Additionally, there is a crosstalk between ER stress and autophagy, a process that is known as reticulophagy or ER-phagy where ER stress elicits a selective form of autophagy, aka ER-phagy, that transpires ER-associated degradation (ERAD) leading to degradation of ER-residing proteins or ER destruction ( 31 ). Early studies showed that induction of reticulophagy by SARS-CoV-2 is essential for viral infection and replication, and ORF3a elicits reticulophagy response and then disrupts ER homeostasis to induce ER stress and inflammatory responses during SARS-CoV-2 infection ( 25 27 ).…”
Section: Introductionmentioning
confidence: 99%